Current condition and future directions for lean construction in highways projects: A small and medium-sized enterprises (SMEs) perspective. Issue 2 (February 2018) - Tezel, Algan; Koskela, Lauri; Aziz, Zeeshan
Abstract: The aim of this study is to identify the parameters defining how Lean Construction (LC) is being implemented (current condition) and how LC can be further promoted (future direction) from a Small-Medium Sized Enterprises (SMEs) perspective. Although SMEs constitute the largest group in construction supply chains, LC, as an emerging phenomenon in civil construction project management, has been rarely investigated from an SMEs perspective. Also, overlooking the more macro factors like project governance and supply chain management, LC deployments have been mainly discussed from a production process perspective to date. After a review of the extant literature and 20 interviews with managers from the highways sector, a list of 31 current condition and 40 future direction statements were produced, classified under the delivery, process, training, project governance and supply chain related headings and used in a questionnaire survey with 110 responses. The current condition highlights problems like a short-term relations structure, competitive tendering mechanisms, fragmentation, problems in engaging with SMEs for LC, unstandardised LC techniques, and issues with convincing SMEs to deploy LC by demonstrating the business case on mutual benefits. Action items relating to the current project delivery structure were given the highest importance by the supply chain, alongside the LC training and project governance issues for the future of LC at highways SMEs. Additionally, a statistically significant correlation was identified among many future action items. Highlights: Main parameters defining the current condition of LC at highways SMEs: SMEs'' current inability to affect the design phase, the focus of the main client (Highways England) being on Tier 1s and large Tier 2s for Lean Construction, SMEs already doing some process based improvements even though not labelled "Lean", lack of in-house Lean Construction training mechanisms at SMEs and the limited use of Building Information Modeling (BIM) as an enabler for Lean Construction and information flow. Most agreed future directions (action items) for LC at highways SMEs: forming longer term alliances with SMEs for Lean Construction, establishing earlier engagement with SMEs, higher certainty, increasing SMEs'' ability to affect the design phase, and that the SMEs'' need to see the business case for Lean Construction.